Q: What is the solution of x plus y equals -2 and 2x plus 3y equals -9?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x + 5y = 16 -2x - 3y = -14 2y = 2 y = 1 / x = 5.5 (5.5,1) or (5 1/2,1)

2x-11

-2x plus 3y equals 1

x = 3 and y = 2

x - 3y = -3: multiply by -2 giving -2x + 6y = 6, but -2x + 6y = 12 so we have a problem! Misprint?

Related questions

2x plus 3y

2x + 5y = 16 -2x - 3y = -14 2y = 2 y = 1 / x = 5.5 (5.5,1) or (5 1/2,1)

2x-11

-2x plus 3y equals 1

x = 3 and y = 2

(2,7)

x - 3y = -3: multiply by -2 giving -2x + 6y = 6, but -2x + 6y = 12 so we have a problem! Misprint?

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

2x-3y=13

How do you add 2x plus 3y equals 18 in 5x-y equals 11

6x plus 3y minus 2x plus 5y equals 4x plus 8y.

2x - y = 15 2x + 3y = -21 As you observe both equations (having different slopes), you see that the system is consistent, and it has only one solution.